91 Meta-Analysis of 4 Trials: The Effect of Multi-Enzyme Containing Xylanase, β-glucanase, Amylase and Protease on Growth Performance in Weaned Pigs. (12th April 2022) - Velayudhan, Deepak; Li, Wenting; Dusel, Georg; Gracia, Marta I; Kumar, Arun; Shoesmith, Ellie; Vinyeta, Ester; Adeola, Olayiwola; Marchal, Leon
Abstract: A meta-analysis was conducted to evaluate the effect of a multi-enzyme complex (MEC) on growth performance in weaned piglets [initial body weight (BW) of 7.6±1.2 kg]. Database was constructed using 4 unpublished studies, contributing 306 data points. The dietary treatments consisted of a conventional diet (CC) with highly digestible nutrients, a high-fiber, low-digestible protein diet (NC), and the NC supplemented with MEC. All diets were corn/wheat/soybean meal based, formulated to meet or exceed NRC specification for weaned piglets. The NC contained ingredients such as barley, distiller's dried grains with solubles, wheat middling, rye and rapeseed meal depending on the geographic location of the study. In all studies, MEC provided 4, 000 U/kg Xylanase, 200 U/kg β-glucanase, 100 U/kg Amylase, and 2, 000 U/kg Protease. All diets contained 750 FTU/kg of a commercial Buttiauxella phytase. Piglets were fed experimental diets over 2 phases for 42 d, from d 1 of weaning. Growth performance was recorded bi-weekly. Data were analyzed using Mixed Model by JMP 14.0. The average daily gain of piglets fed MEC supplemented diets was increased by 7.4% vs NC (P = 012) during phase 1. The final BW (d 42) was improved by 1.1 kg (4.1%; P = 0. 037) in piglets fed MEC supplemented diets compared with NC. Respective improvements ( P < 0.05) in feed conversion ratio during phase 1 and overall were 11% (16 points) and 4.4% (7 points) in MEC supplemented diets when compared with NC, which indicates better nutrient digestibility. In conclusion, supplementing a high fiber weaner diets with a multi-enzyme complex improved final BW and feed efficiency in piglets.